ABCC8 Gene Factors in Maturity-Onset Diabetes of The Young (MODY): Literature Review - Setyawati, Tri; Walanda, Ryka Marina; Sulisda, Sulisda; Putrie, Intania Riska; Oktafiani, Devi (Journal of Health and Nutrition Research, 2025)
Maturity-Onset Diabetes of the Young (MODY) is a monogenic form of diabetes caused by single-gene mutations affecting insulin secretion, often presenting in young individuals. Mutations in the ABCC8 gene (MODY12), encoding the SUR1 subunit of the pancreatic β-cell K-ATP channel, are a known cause, though relatively rare (1-3% prevalence). This literature review summarized cases of ABCC8-MODY, detailing genetic/clinical features, differentiating it from Type 1 (T1DM) and Type 2 (T2DM) diabetes, and outlining treatments. A Google Scholar search (2020-2024) using keywords "ABCC8 gene," "diabetes," and "young age," followed by screening based on specific inclusion/exclusion criteria, yielded 7 relevant articles from an initial 1,010. The ABCC8 gene is crucial for insulin secretion via the K-ATP channel; mutations cause β-cell dysfunction and MODY12 with variable phenotypes. Misdiagnosis as T1DM/T2DM is frequent. Key MODY features include young onset (<25-35 years), strong family history, absence of pancreatic autoantibodies, persistent endogenous insulin production (detectable C-peptide), and often, high sensitivity to sulfonylureas (SUs). Accurate diagnosis requires meticulous history, clinical assessment, and definitive molecular genetic testing (e.g., NGS). Notably, patients with ABCC8-MODY typically respond well to SU therapy, making early, correct diagnosis vital for appropriate management. Identifying these genetic defects is paramount for distinguishing MODY from other diabetes types and optimizing patient care based on specific underlying pathophysiology and therapeutic responsiveness